Socio economic analysis of emigration from Kerala to the United States of America - Abdul Rasheed M (Department of economics EMEA college of arts and science, 2024)
The socio-economic dynamics of emigration from Kerala to the United States of America exhibit a unique migration pattern compared to migration to the Gulf region. This is because migration to the US is characterized predominantly by a skilled emigrant population. This study has four objectives: (1) Analysing the socio- economic characteristics of both migrants and non-migrants, (2) Identifying the accelerators and brake pedal of the Indian economy in the context of migration, (3) Evaluating the endowments and capabilities that help to respond to the factors contributing to migration from Kerala, and (4) Analysing the impact of emigration on migrant households. This study involves a comparative analysis of migrant and non-migrant households. The literature shows that most of the research on migration addresses the reasons for emigration, the impact of remittances on the economy, return migration and the influence of migration on the psychological well-being of the parents left behind. All these studies were exclusively focused on migration to the Gulf region. Examining emigration to the USA, unfolding the inner dynamics and rationalising the nuances using suitable theoretical underpinnings to explain the underlying factors is a less ventured arena. Therefore, it is crucial to investigate emigration from Kerala to the US, its implications, its determinants and the impact on migrant households. Data for this study were collected from two districts of Kerala, Pathanamthitta and Kottayam, which are considered significant migrant pockets to the US. The total sample size for this study is 358, comprising 143 migrant households and 215 non-migrant households. A descriptive analysis is carried out to trace the socio-economic characteristics of both migrants and non-migrants. The analysis reveals that younger individuals, particularly those around thirty years old, are more likely to migrate with males dominating the migrant demographic. Christians form the majority of the migrant community, likely due to established social networks in the US. Most migrants hold postgraduate degrees, indicating a significant brain drain and the majority work in nursing, highlighting the high demand for healthcare professionals in the US. The notable thing is that despite their educational qualifications, some migrants face the problem of underemployment. In the context of migration, this phenomenon is called brain waste. Additionally, professions like doctors, engineers, business, company lawyers and system analysts are solely occupied by the Male population. Christians dominate in jobs like anesthesia technician, legal advisor,system analyst, accountant and microbiologist. The characteristics of non-migrants reveal that the majority are younger to middle-aged and belong to the Hindu community. Both Hindus and Christians are predominantly involved in rubber tapping and degree holders often work in jobs like sales and construction, highlighting employment challenges among the educated non-migrant community. To examine the second objective, the Auto Regressive Distributed Lag model (ARDL) was employed. The result of the ARDL shows that emigration is negatively correlated with India‟s economic growth but positively correlated with human capital development and population density. This suggests that increasing domestic economic opportunities may reduce the pace of emigration from India to the USA, thereby addressing the problem of brain drain. The Logistic regression model (LOGIT) is used to analyse the third objective, the influence of individual (age & education), social (religion & social networks), family (land owned) endowments and gender on emigration from Kerala to the USA. Endowment means anything that a person possesses and that enhances the choice of the people. The results indicate that compared to females the probability of emigration among males is high, and the Christian community is more likely to migrate compared to non-Christians. Moreover, the results show that pre-existing social networks in the USA significantly increase the probability of migration. The overall result of LOGIT shows that social and human capital factors, including educational attainment and family resources, are crucial in migration. Finally, this study examines the impacts of emigration on migrant households. The impacts of emigration on migrant households are quite visible, with increased asset accumulation and a higher standard of living in the post-migration period, caused by remittances and increased earnings. Emigration increases the asset holdings of migrant households compared to non-migrant households and also enhances the standard of living through spillover effects. However, no significant differences in the standard of living were found among different religious communities within migrant households. These findings underline the positive effects of migration on the growth of assets and living standards of migrant households after migration.
Keywords: Brain Drain; Brain Gain; Accelerator; Brake Pedal; Human Development